Impact of work-family conflict on work engagement among female university teachers: Evidence from China. - Xitao Dong; Xiaona Guo; Yanyan Fu; Tingting Fu (PLoS ONE)
University faculty, including female teachers, often face work-family conflict (WFC) which subsequently impacts their work engagement. This study analyzes data from 489 questionnaires using Mplus 8.0 to explore the internal mechanisms linking WFC and work engagement among female faculty. The study uncovers several significant findings: (1) a negative correlation between WFC and female teachers' work engagement; (2) job burnout mediates this relationship; (3) job crafting and grit both moderate this relationship. These insights enrich human resource management theory and offer valuable guidance for the development and implementation of university management systems.